(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The article discusses the clinical picture, diagnosis, effectiveness and disadvantages of various modern, minimal invazive methods of surgical treatment of malignant gastric ulcers. The basis of scientific research is diagnostic and varied surgical tactics for treating patients in the Department of Thoracoabdominal Oncology Surgery of the State Institution “RSNPMCCH named after. acad. V.Vakhidova".